Heart Transplantation From DCD Donors in Australia: Lessons Learned From the First 74 Cases. Issue 2 (31st August 2022) - Joshi, Yashutosh; Scheuer, Sarah; Chew, Hong; Ru Qiu, Min; Soto, Claudio; Villanueva, Jeanette; Gao, Ling; Doyle, Aoife; Takahara, Shingo; Jenkinson, Charles; Vaidhya, Nikunj; Matsumoto, Yorihiko; et al.
Abstract : Heart transplantation from donation after circulatory death (DCD) donors has the potential to substantially increase overall heart transplant activity. The aim of this report is to review the first 8 y of our clinical heart transplant program at St Vincent's Hospital Sydney, to describe how our program has evolved and to report the impact that changes to our retrieval protocols have had on posttransplant outcomes. Since 2014, we have performed 74 DCD heart transplants from DCD donors utilizing a direct procurement protocol followed by normothermic machine perfusion. Changes to our retrieval protocol have resulted in a higher retrieval rate from DCD donors and fewer rejections of DCD hearts during normothermic machine perfusion. Compared with our previously reported early experience in the first 23 transplants, we have observed a significant reduction in the incidence of severe primary graft dysfunction from 35% (8/23) to 8% (4/51) in the subsequent 51 transplant recipients ( P < 0.01). The only withdrawal time interval significantly associated with severe primary graft dysfunction was the asystolic warm ischemic time: 15 (12–17) versus 13 (11–14) min ( P < 0.05). One- and 5-y survival of DCD heart transplant recipients was 94% and 88%, comparable to that of a contemporary cohort of donation after brain death recipients: 87 and 81% ( P -value was not significant). In conclusion, heart transplantation from DCD donors has become a major contributor to our overall transplant activity accounting for almost 30% of all transplants performed by our program in the last 2 y, with similar DCD and donation after brain death outcomes. Abstract :